Penerapan Vertikultur sebagai Inovasi Pertanian Lahan Kering Untuk Meningkatkan Produksi Sayuran dan Pendapatan KWT Suka Maju NTT - Agustinus Nubatonis; Boanerges Putra Sipayung; Wilda Lumban Tobing; Kristoforus Wilson Kia; Kristina Kolo; Maria Magdalena Bato (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to increase vegetable production and the income of the Suka Maju Women Farmers Group in East Nusa Tenggara through the application of vertical cultivation technology as a sustainable agricultural innovation for dryland areas. The program was implemented through extension activities and training involving the village government, agricultural extension officers, and community members. The service stages included the socialization of the vertical cultivation concept, construction of installations using PVC pipes, modification of planting media based on local resources, planting and maintenance, harvesting, agribusiness management training, and program evaluation through observations and interviews. The results showed that the implementation of vertical cultivation was able to address various limitations of dryland agroecosystems, improve labor efficiency, reduce input use, and create wider marketing opportunities. Harvest results indicated an increase in production and income of more than 50% compared with conventional systems. Vertical cultivation technology proved effective as a dryland agricultural innovation capable of sustainably improving the production and income of the Suka Maju Women Farmers Group.